Productive consequences of fasting neonatal chicks of different genetic constitutions for growing - Gonzales, E [UNESP] (2008)
The study was designed to evaluate the productive consequences of fasting neonatal chicks obtained from strains genetically divergent for growing. Four hundred eight chicks from three strains, 160 from breeders selected for high growth rate and excellent feed conversion ratio (Cobb 500), 160 from breeders not selected for fast growth (JA57), and 160 from a white egg layer strain (Hy-Line W98) were allotted in a 3 (strain) x 2 (fasting period - 8 and 36h after hatching) factorial arrangement with 5 replicates of 16 chicks each. Immediately after hatching, all chicks had similar (P>0.05) relative yolk sac weights (14.13%, 14.50%, and 15.49% for Hy-Line, Cobb, and JA57, respectively). The yolk sac retractions were proportionally higher for Cobb and JA57 chicks up to 144 h (6 days) after placement, but were not influenced by 36h of feed fasting. At 7 and 14 days of age only Cobb chicks had their body weight and weight gain significantly (P<0.05) depressed by 36h feed fasting after hatching. Results indicate that broiler chicks with intense initial growth rates (Cobb 500) need an outstanding nutritional supply, either from exogenous (feed) or endogenous (residual yolk) sources, to achieve a final weight compatible with their genetic constitution. For slow-growing chicks (Hy-Line), nutritional supplementation via yolk sac seems to be more important than exogenous supply (feed) of nutrients during the neonatal period.